Ideas production in emerging economies - Kul B. Luintel; Mosahid Khan (Cardiff University, Cardiff Business School, 2012)
We model 'new ideas' production in a panel of 17 emerging countries. Our results reveal: (i) ideas production is duplicative, (ii) externality associated with domestic knowledge stocks is of above unit factor proportionality, (iii) OECD countries raise the innovation-bar for emerging countries, (iv) there is no significant knowledge diffusion across emerging countries, and (v) growth in emerging countries appear far from a balanced growth path.
Keywords: C2; O3; O4; 330; Ideas Production; Knowledge Diffusion; Panel Co-integration